Doomsday movements in Africa: Restoration of the Ten Commandments of God - Venter, Pieter M. (HTS teologiese studies, 2006)
This article investigates Kibwetere’s Movement for the Restoration of the Ten Commandments of God. A brief summary of the Movement’s short history is followed by an outline of the movement’s main beliefs. This Ugandan cult’s socio historic context is thereupon analyzed. The cult’s document, “A Timely Message”, is summarized and their relationship with a similar Marian movement in Australia is indicated. Finally, the phenomenon of their suicide is discussed in terms of doomsday apocalypticism and depicted as a result of Roman Catholic apocalyptic thinking.